The effect of honeybush (Cyclopia subternata) extract in dry-cured and fermented warthog salami with reduced added nitrate - Smit, Paula (Stellenbosch : Stellenbosch University, 2020)
Thesis (MScFoodSc)--Stellenbosch University, 2020.